Imaging in Testicular Tumors - Eftekhari, Farzin (2023)
It is the purpose of this article to describe and discuss the relative roles of these imaging modalities in the diagnosis of testicular neoplasms and work-up of metastatic disease. The ultimate role of MRl has yet to be evaluated. Other imaging modalities such as chest radiography, radionuclide scanning, and brain CT scanning may be performed as the need arises. Special procedures such as arteriography and venography are occasionally performed in search of undescended testicles complicated by malignancy.